Ideology and social change in Latin America - Nash, June C., 1927-; Corradi, Juan E., 1943-; Spalding, Hobart (Routledge library editions. Development ;, 2011)
First published in 1977, this reissue contains original articles by contemporary leading scholars in the field of Latin American politics on a range of topics including: working class organisation, populism and US labour imperialism. It will be of interest to anthropologists, students of political science and specialists in Latin American studies.